2019
DOI: 10.1002/eji.201948126
|View full text |Cite
|
Sign up to set email alerts
|

Naturally processed HLA‐DR3‐restricted HHV‐6B peptides are recognized broadly with polyfunctional and cytotoxic CD4 T‐cell responses

Abstract: Human herpes virus 6B (HHV‐6B) is a widespread virus that infects most people early in infancy and establishes a chronic life‐long infection with periodic reactivation. CD4 T cells have been implicated in control of HHV‐6B, but antigenic targets and functional characteristics of the CD4 T‐cell response are poorly understood. We identified 25 naturally processed MHC‐II peptides, derived from six different HHV‐6B proteins, and showed that they were recognized by CD4 T‐cell responses in HLA‐matched donors. The pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 100 publications
4
27
0
Order By: Relevance
“…Also, the distribution of peptides eluted from the beads-only column of the membrane preparation looked similar to the beads-only eluted peptides of the whole cell preparation (Supplementary Figure S3B). These results indicated that a membrane fractionation strategy as used previously (13,36,37) was not helpful in removing the non-specific peptides. Second, we tested whether restricting the analysis to peptides identified reproducibly in every sample would help to remove non-specific peptides, with the idea that the non-specific peptides might be present sporadically as a result of low-frequency random binding or sampling events.…”
Section: Non-specific Peptidesmentioning
confidence: 88%
“…Also, the distribution of peptides eluted from the beads-only column of the membrane preparation looked similar to the beads-only eluted peptides of the whole cell preparation (Supplementary Figure S3B). These results indicated that a membrane fractionation strategy as used previously (13,36,37) was not helpful in removing the non-specific peptides. Second, we tested whether restricting the analysis to peptides identified reproducibly in every sample would help to remove non-specific peptides, with the idea that the non-specific peptides might be present sporadically as a result of low-frequency random binding or sampling events.…”
Section: Non-specific Peptidesmentioning
confidence: 88%
“…The ancestry variation in individuals with SLE, as said before, could mean that some non-autochthonous HLA alleles have been conserved because these alleles represent an immunogenetic advantage, as demonstrated for HLA-DRB1 ∗ 03. For instance, some naturally processed HLA-DR3-restricted Human herpesvirus 6B (HHV-6B) peptides are recognized broadly with polyfunctional and cytotoxic CD4 T-cell responses ( Becerra-Artiles et al, 2019 ). However, this convenient immunogenetic mechanism for clearing infections might be the detonator for immunological hyperreactivity, which marks the onset of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…They were able to activate T cells recruiting from CD3+ and CD4+ subpopulations. In natural conditions, observed T-cells reactivity toward presented antigens, identified during the investigation, allows controlling HHV-6B infection at a reasonable level (Becerra-Artiles et al, 2019). Ternette et al (2016) immunoprecipitated peptides bound to HLA class I complexes from HIV-1-infected primary CD4+ T cells and C8166 cell lines, and further identified those by LC-MS/MS.…”
Section: A Vaccine Designmentioning
confidence: 92%